Long Non-coding RNAs RN7SK and GAS5 Regulate Macrophage Polarization and Innate Immune Responses - Ahmad, Imran; Valverde, Araceli; Naqvi, Raza Ali; Naqvi, Afsar R. (Frontiers in Immunology, 2020)
Macrophages (Mφ) are immune cells that exhibit remarkable functional plasticity. Identification of novel endogenous factors that can regulate plasticity and innate immune functions of Mφ will unravel new strategies to curb immune-related diseases. Long noncoding RNAs (lncRNA) are a class of endogenous, non-protein coding, regulatory RNAs that are increasingly being associated with various cellular functions and diseases. Despite their ubiquity and abundance, lncRNA-mediated epigenetic regulation of Mφ polarization and innate immune functions is poorly studied. This study elucidates the regulatory role of lncRNAs in monocyte to Mφ differentiation, M1/M2 dichotomy and innate immune responses. Expression profiling of eighty-eight lncRNAs in monocytes and in vitro differentiated M2 Mφ identified seventeen differentially expressed lncRNAs. Based on fold-change and significance, we selected four differentially expressed lncRNAs viz., RN7SK, GAS5, IPW and ZFAS1 to evaluate their functional impact. LncRNA knockdown was performed on day 3 M2 Mφ and the impact on polarization was assessed on day 7 by surface marker analysis. Knockdown of RN7SK and GAS5 showed downregulation of M2 surface markers (CD163, CD206 or Dectin) and concomitant increase in M1 markers (MHC II or CD23). RN7SK or GAS5 knockdown showed no significant impact on CD163, CD206 or CD23 transcripts. M1/M2 markers were not impacted by IPW or ZFAS1 knockdown. Functional regulation of antigen uptake/processing and phagocytosis, two central innate immune pathways, by candidate lncRNA was assessed in M1/M2 Mφ. Compared to scramble, enhanced antigen uptake and processing was observed in both M1/M2 Mφ transfected with siRNA targeting GAS5 and RN7SK but not IPW and ZFAS1. In addition, knockdown of RN7SK significantly augmented uptake of labelled E. coli in vitro by M1/M2 Mφ, while no significant difference was in GAS5 silencing cells. Together, our results highlight the instrumental role of lncRNA (RN7SK and GAS5)-mediated epigenetic regulation of macrophage differentiation, polarization and innate immune functions.